Effects of the Amount of Dietary Nitrates Consumption on Endurance Performance: 膳食補充硝酸鹽對新加坡休閒運動員的耐力運動表現的影響 - WAH, Vera; KOH, Sarah; NG , Denise; WANG , Grace; QUEK, Steven (Asian Journal of Physical Education & Recreation, 2017)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The current study examined the effects of dietary nitrates consumption on endurance performance of recreational athletes in Singapore. The consumption of dietary nitrates has been shown to reduce whole body oxygen cost of submaximal exercise and enhance tolerance to high intensity exercise. Beetroot, which is concentrated in dietary nitrates, is a popular natural food that has been associated with enhancement of endurance performance. Majority of studies on the effects of beetroot consumption on endurance performance have been carried out using 500ml of beetroot juice. To make the juice more palatable, and hence encourage consumption by the young athletes, this study used 250ml of beetroot juice, mixed with 250ml of apple and orange juice. 23 subjects (10 males and 13 females aged between 12 and 24) were recruited for the study. Subjects performed the Multi-stage Fitness Test (MST) on two separate days after consuming 500ml of Apple and Orange (AO, Control Group) juice or Apple, Beetroot and Orange (ABO, Experimental Group) juice. The VO2 max obtained from both tests were compared using a Paired Sample t-test. Paired Sampled t-test (t = -0.08, p < 0.05) showed that there was no significant difference between the VO2 max of the experiment group and the VO2 max of the control group. Results of the present study suggests that 250ml of beetroot juice combined with 250ml of apple and orange juice did not result in significant differences in endurance performance. 本文旨在探討膳食補充硝酸鹽如何影響新加坡休閒運動員的耐力運動表現。過去研究顯示在日常飲食內攝取膳食硝酸鹽， 可以降低亞極量運動的氧價，並增強對激烈運動的耐受力。由於甜菜根高含硝酸鹽，眾人深信食用甜菜根是能提升耐力運動的 表現。多數研究在實驗內利用500毫升的甜菜根汁來探測它對耐力表現。為了鼓勵年輕運動員飲用甜菜根汁，本研究混合了250 毫升的甜菜汁及250毫升的蘋果和橙汁。23名12歲至24歲的休閒運動員(10名男性與13名女性)參與本研究。實驗在分別兩天喝 了500毫升蘋果與橙汁(控制組)或500毫升蘋果，橙與紅甜菜根汁(實驗組)之後，進行了多階段體能測試(Multi-stage Fitness Test 短稱 MST)。實驗採用相似樣本T鑒定法比較從這兩次MST測試到的最大攝氧量。相似樣本T鑒定(t=-0.08, p<0.05)顯 示控制組與實驗組的VO2 max之間沒有顯著的差異。因此，本研究顯示250毫升甜菜根加入250毫升蘋果和橙混合汁對耐力運動 表現沒有顯著的影響。本文旨在探討膳食補充硝酸鹽如何影響新加坡休閒運動員的耐力運動表現。過去研究顯示在日常飲食內攝取膳食硝酸鹽， 可以降低亞極量運動的氧價，並增強對激烈運動的耐受力。由於甜菜根高含硝酸鹽，眾人深信食用甜菜根是能提升耐力運動的 表現。多數研究在實驗內利用500毫升的甜菜根汁來探測它對耐力表現。為了鼓勵年輕運動員飲用甜菜根汁，本研究混合了250 毫升的甜菜汁及250毫升的蘋果和橙汁。23名12歲至24歲的休閒運動員(10名男性與13名女性)參與本研究。實驗在分別兩天喝 了500毫升蘋果與橙汁(控制組）或500毫升蘋果，橙與紅甜菜根汁(實驗組)之後，進行了多階段體能測試(Multi-stage Fitness Test 短稱 MST)。實驗採用相似樣本T鑒定法比較從這兩次MST測試到的最大攝氧量相似樣本T鑒定(t=-0.08, p<0.05)顯示控制組與實驗組的VO2 max之間沒有顯著的差異。因此，本研究顯示250毫升甜菜根加入250毫升蘋果和橙混合汁對耐力運動表現沒有顯著的影響。